2005
DOI: 10.1111/j.1460-9568.2005.04057.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling pathological pain by adenovirally driven spinal production of the anti‐inflammatory cytokine, interleukin‐10

Abstract: Gene therapy for the control of pain has, to date, targeted neurons. However, recent evidence supports that spinal cord glia are critical to the creation and maintenance of pain facilitation through the release of proinflammatory cytokines. Because of the ability of interleukin-10 (IL-10) to suppress proinflammatory cytokines, we tested whether an adenoviral vector encoding human IL-10 (AD-h-IL10) would block and reverse pain facilitation. Three pain models were examined, all of which are mediated by spinal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
159
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 196 publications
(175 citation statements)
references
References 82 publications
14
159
0
2
Order By: Relevance
“…Nitric oxide was found to be key in mediating elevations of IL1, TNF and IL6 mRNA and protein in lumbar spinal cord leading to allodynia in gp120-treated animals (Holguin et al, 2004). In addition, IL-1 was shown to be important for the maintenance of neuropathic pain states because established neuropathic pain can be reversed either by proinflammatory cytokine antagonists or by the anti-inflammatory cytokine interleukin-10 (IL10) (Abraham et al, 2004, Johnston et al, 2004, Ledeboer et al, 2007, Milligan et al, 2005a, Milligan et al, 2005b, Milligan et al, 2006a, Milligan et al, 2006b, Plunkett et al, 2001, Sloane et al, submitted, Yu et al, 2003 that inhibits the production and activity of proinflammatory cytokines ). Such results are important when one is considering the potential of targeting proinflammatory cytokines for clinical pain control.…”
Section: Pathological Pain Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide was found to be key in mediating elevations of IL1, TNF and IL6 mRNA and protein in lumbar spinal cord leading to allodynia in gp120-treated animals (Holguin et al, 2004). In addition, IL-1 was shown to be important for the maintenance of neuropathic pain states because established neuropathic pain can be reversed either by proinflammatory cytokine antagonists or by the anti-inflammatory cytokine interleukin-10 (IL10) (Abraham et al, 2004, Johnston et al, 2004, Ledeboer et al, 2007, Milligan et al, 2005a, Milligan et al, 2005b, Milligan et al, 2006a, Milligan et al, 2006b, Plunkett et al, 2001, Sloane et al, submitted, Yu et al, 2003 that inhibits the production and activity of proinflammatory cytokines ). Such results are important when one is considering the potential of targeting proinflammatory cytokines for clinical pain control.…”
Section: Pathological Pain Statesmentioning
confidence: 99%
“…Gene-encoding vectors, such as viral and non-viral vectors to deliver the IL-2, IL-4 or IL-10 gene to the spinal cord to control pain in neuropathic rodent models have been examined and show promise (Hao et al, 2006, Ledeboer et al, 2007, Milligan et al, 2005a, Milligan et al, 2005b, Yao et al, 2003, Yao et al, 2002a, Yao et al, 2002b. For example, spinal cord over-expression of IL-10 controls pain produced by sciatic inflammatory neuropathy and chronic constriction injury (Milligan et al, 2005a, Milligan et al, 2007, Milligan et al, 2005b. The duration of pain control by spinal IL-10 gene therapy was observed from 1-3 months (Milligan et al, 2006a, Sloane et al, submitted).…”
Section: Targeting Activated Glia With Anti-inflammatory Cytokines Tomentioning
confidence: 99%
“…18 In addition, intrathecal administration of the adenovirus expressing IL-10 prevented intrathecal HIV-1 gp 120-induced mechanical allodynia, without affecting basal responses to thermal or mechanical stimuli. 18 IL-2 is an important immuno-regulatory molecule in the central nervous system (CNS). 19,20 IL-2 and IL-2 receptors are widely distributed in rat CNS 21 and evidence showed that IL-2 had an antinociceptive effect in both central and peripheral nervous system 22 and inhibited nociceptive responses of spinal dorsal horn neurons.…”
Section: Adenovirus Vectormentioning
confidence: 99%
“…4 Interleukin (IL)-10, an anti-inflammatory cytokine is known to suppress the production of proinflammatory cytokines. 17,18 Acute intrathecal administration of rat IL-10 protein itself briefly reverses sciatic chronic constriction injury (CCI)-induced mechanical allodynia and thermal hyperalgesia. 17,18 Watkins and coworkers demonstrated that intrathecal administration of adenoviral vector encoding for IL-10 injected over lumbosacral spinal cord led to elevated lumbosacral cerebrospinal fluid levels of IL-10, prevented sciatic nerve inflammation [sciatic inflammatory neuropathy (SIN)]-induced mechanical allodynia and attenuated chronic SINinduced territorial, extraterritoral, and mirror-imaging mechanical allodynia.…”
Section: Adenovirus Vectormentioning
confidence: 99%
See 1 more Smart Citation